2016
DOI: 10.1063/1.4944418
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of transferred charges across the heterointerface between perovskite transition metal oxides LaNiO3 and LaMnO3

Abstract: To investigate the interfacial charge-transfer phenomena between perovskite transition metal oxides LaNiO3 (LNO) and LaMnO3 (LMO), we have performed in situ x-ray absorption spectroscopy (XAS) measurements on LNO/LMO multilayers. The Ni-L2,3 and Mn-L2,3 XAS spectra clearly show the occurrence of electron transfer from Mn to Ni ions in the interface region. Detailed analysis of the thickness dependence of these XAS spectra has revealed that the spatial distribution of the transferred charges across the interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 39 publications
5
20
0
Order By: Relevance
“…The values extracted from XPS/XAS studies only account for about 70% of the interpolated value, which is understandable as those techniques can penetrate beyond the interfacial atomic layer. The measurements are thus probing a spatially weighted average of the valence change, which can extend over a length scale on the order of L CS from the interface . The spatial variation of charge transfer is clearly demonstrated in the calculations of superlattices with a larger periodicity.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…The values extracted from XPS/XAS studies only account for about 70% of the interpolated value, which is understandable as those techniques can penetrate beyond the interfacial atomic layer. The measurements are thus probing a spatially weighted average of the valence change, which can extend over a length scale on the order of L CS from the interface . The spatial variation of charge transfer is clearly demonstrated in the calculations of superlattices with a larger periodicity.…”
mentioning
confidence: 96%
“…In this scenario, to achieve a tailored carrier density profile in SNNO, it is critical to have a strong overlap between the charge‐transfer region from the SNNO/LSMO interface and the charge screening region from the PZT/SNNO interface. Previous dynamic mean field theory studies of ABO 3 ‐type correlated oxide superlattices have shown that the spatial mobile electron density variation on the B ‐site cations depends critically on the relative strength of electron hopping energy and the Coulomb interaction . The characteristic length for charge transfer is the Coulomb charge screening length, defined as LCS=κε0ta2/e2, where ε 0 , t , and a are the vacuum permittivity, transfer integral, and lattice parameter, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2. Here, we focus on the Ni-2p XAS spectra at the Ni-L 2 edge because the Ni-L 3 edge structure partially overlaps with the very strong La-M 4 absorption edge owing to the close proximity of the two energy levels 30,31 . In order to examine the valence of Ni ions in the thin films, the energy of Ni 3+ (871.9 eV) and Ni 2+ (870.3 eV) signals in perovskite nickelates 32 are indicated by solid lines.…”
Section: A X-ray Absorption Spectroscopymentioning
confidence: 99%
“…Superlattices composed of manganites and nickelates are a paradigmatic venue for efforts to discover and understand emergent interface magnetism, motivated by the complex magnetic order and phase diagram of its bulk constituents [10,11]. In fact, this system harbors fascinating phenomena, such as exchange bias and interfacial electronic reconstructions [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Recently, a highly unusual magnetic coupling between ferromagnetic (LSMO) 9 layers was observed in [001]-oriented (La 2/3 Sr 1/3 MnO 3 ) 9 /(LaNiO 3 ) n [(LSMO) 9 /(LNO) n , n = 1 − 9], in which the coupling angle between (LSMO) 9 layers varies between zero and 130 • as a function of n ( Fig.…”
mentioning
confidence: 99%